2020
DOI: 10.1073/pnas.1919306117
|View full text |Cite
|
Sign up to set email alerts
|

Constructing artificial respiratory chain in polymer compartments: Insights into the interplay betweenbo3oxidase and the membrane

Abstract: Cytochromebo3ubiquinol oxidase is a transmembrane protein, which oxidizes ubiquinone and reduces oxygen, while pumping protons. Apart from its combination with F1Fo-ATPase to assemble a minimal ATP regeneration module, the utility of the proton pump can be extended to other applications in the context of synthetic cells such as transport, signaling, and control of enzymatic reactions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(118 citation statements)
references
References 87 publications
2
100
2
Order By: Relevance
“…In 2018, we achieved increased stability of cytochrome bo 3 reconstituted in hybrid vesicles up to 500 days [197]. Similarly, recent work from Dimova group showed that functional integration of cytochrome bo 3 oxidase in synthetic membranes made of PDMS-g-PEO was capable of lumen acidification and such reconstituted system showed to increase the active lifetime and resistance to free radicals [198]. In 2017, Otrin et al [199] demonstrated a similar ability to store gradients by reconstituting cytochrome bo 3 together with an ATP synthase in hybrid vesicles constituted of the same copolymer, PDMS-g-PEO.…”
Section: Extending the Lifetime Of Membrane Enzymesmentioning
confidence: 63%
“…In 2018, we achieved increased stability of cytochrome bo 3 reconstituted in hybrid vesicles up to 500 days [197]. Similarly, recent work from Dimova group showed that functional integration of cytochrome bo 3 oxidase in synthetic membranes made of PDMS-g-PEO was capable of lumen acidification and such reconstituted system showed to increase the active lifetime and resistance to free radicals [198]. In 2017, Otrin et al [199] demonstrated a similar ability to store gradients by reconstituting cytochrome bo 3 together with an ATP synthase in hybrid vesicles constituted of the same copolymer, PDMS-g-PEO.…”
Section: Extending the Lifetime Of Membrane Enzymesmentioning
confidence: 63%
“…Even after three complete light-dark cycles, we observed only little decrease in the pH gradient. Compared to previous reports where proton pumps were reconstituted in lipid vesicles, [7,27] we could achieve faster and higher pH gradients using genetically engineered E. coli. Moreover, the use of E. coli circumvented the need for cumbersome protein purification and reconstitution to prepare proteoliposomes, [28] which highlights a key advantage of merging top-down and bottom-up synthetic biology.…”
Section: Top-down Engineering Of E Coli For Light-harvestingmentioning
confidence: 87%
“…[ 130–135 ] A comprehensive comparison between lipid and polymer vesicles from physical properties to cellular function reconstructions can be found in refs. [ 136,137 ] .…”
Section: Compartmentalization Via Interfaces Of Multiphase Systemsmentioning
confidence: 99%
“…[ 161 ] Surprisingly, hybrid vesicles with intermediate lipid/copolymer ratios can be more permeable to ion transport than pure lipid and polymer vesicles, arising from dynamic equilibrium of vesicles and tubular micelle formations. [ 137,163 ] Hybrid vesicles also allow the accommodation of hydrophobic proteins and nanoparticles more easily than pure lipid vesicles, [ 44,167 ] and hydrophilic nanoparticles cannot be accommodated since they appears either in the interior or the outlier of the bilayer of the vesicle. The size and surface charge of the hydrophobic nanoparticle affect the topology of the bilayer vesicle differently.…”
Section: Compartmentalization Via Interfaces Of Multiphase Systemsmentioning
confidence: 99%
See 1 more Smart Citation